Ischaemic stroke or TIA in older subjects associated with impaired dynamic blood pressure control in the absence of severe large artery stenosis. - FAGAN, ANDREW; KENNY, ROSE; MEANEY, JAMES (My University, 2015)
Background: older subjects may require higher baseline blood pressures to maintain cerebral perfusion. We investigated whether episodic hypotension is associated with tissue infarction in subjects with syncopal symptoms at stroke onset. Methods: over 30 months, all acute strokes/TIAs were prospectively screened for symptoms of syncope or presyncope at stroke onset. Subjects with severe large vessel stenosis were excluded, while cases were referred for syncope unit investigation. All underwent 1.5 T MRI acutely, and suspected borderzone infarctions (BZI) were confirmed through Matlab-derived perfusion software. Case-control comparison was derived from stroke controls with no prior syncope history. Results: thirty-eight of 772 stroke patients described presyncope or syncope at stroke onset and had patent large vessels (4.9% of all strokes). Median age was 72 years (IQR 21.4). Twenty-two patients (58%) were prescribed antihypertensive agents at symptom onset. Twenty-six (68.4%) reported focal neurology <24 h in duration. 63.2% (n = 24) of cases reported prior syncope history, compared with 33% (N = 103) of controls, P < 0.001. Cases exhibited greater orthostatic BP drop than controls, P < 0.05 Twenty-four patients were diagnosed with vasovagal syncope through head-up tilt symptom reproduction, 9 with orthostatic hypotension, 4 with cardiac syncope and 1 with carotid sinus syndrome. Nineteen (50%) patients had an acute infarct on MRI, 14 of these were in the arterial borderzone (73.6%). The BZI group were significantly older than the non-BZI group, 79.2yrs versus 63.3 yrs, P = 0.002. Conclusion: subjects reporting hypotensive symptoms at stroke onset have a higher prevalence of borderzone infarction, despite being normotensive or hypertensive at baseline. © The Author 2015. Published by Oxford University Press on behalf of the British Geriatrics Society
PUBLISHED
Keywords: Neuroimaging; Older people; Stroke; Syncope; Neuroimaging; Older people; Stroke; Syncope; Ageing; Neuroscience; MRI